INSTITUTIONAL LOGIC HUKUM PANGAN HALALAN THAYYIBAN MASYARAKAT BANTEN - Ikomatussuniah; Muhyi Mohas (International Journal Mathla’ul Anwar of Halal Issues, 2022)
Studies related to the institutional logic of the food law with the concept of halalan thayyiban in Banten have not been found in the literature. Therefore, this study is related to the institutional logic of the food law based on the concept of halalan thayyiban in the Banten community about the meaning and discourse of the paradigm, the behavior of the community in purchasing food, the challenges and implementation of the halalan thayyiban food law. A deductive research strategy is used based on Institutional logic theory by using primary and secondary data. Furthermore, qualitative data analysis was carried out in an analytical descriptive. The results of the study are customary law as taken for granted pillar of the food system with the concept of halalan thayyiban is very dominant in people's lives in meeting their food needs. Furthermore, the law of food security as a normative pillar implemented through irrigation and distribution of halalan thayyiban food and controlled by the community. Then, the government plays an active role in regulating the food security system through the issuance of food regulations as an implementation of regulative pillars in increasing food self-sufficiency, and customary law as local wisdom applies in some regions.